Pain Intensity as a Moderator of the Association between Opioid Use and Insomnia Symptoms among Adults with Chronic Pain - Miller, Mary Beth (Sleep Med, 2018)
OBJECTIVE: Research documenting the impact of opioid use on sleep among individuals with chronic pain has been mixed. This study aimed to determine if pain intensity moderates the association between opioid use and insomnia symptoms among adults with comorbid symptoms of insomnia and chronic widespread pain. METHODS: Participants (N=144; 95% female; mean age=51.6, SD=11.4) completed assessments of insomnia symptoms, pain, and use of sleep/pain medication. Multiple regression was used to determine if pain intensity moderates the association between opioid use (yes/no) and sleep onset latency (SOL), wake after sleep onset (WASO), sleep quality, or time in bed. Analyses controlled for gender, symptoms of sleep apnea, symptoms of depression, use of sleep medication (yes/no), and use of non-opioid pain medication (yes/no). RESULTS: Stronger pain intensity was associated with longer self-reported WASO and worse sleep quality, independent of opioid use. Conversely, opioid use was associated with longer time in bed, independent of pain intensity. Opioid use and pain intensity interacted in the prediction of SOL, such that opioid use (vs. non-use) was associated with longer SOL in the context of mild but not moderate to severe pain intensity. CONCLUSIONS: Opioid use was associated with more difficulty falling asleep among adults with chronic pain; however, this cross-sectional effect was only significant among those reporting lower pain intensity. Authors speculate that this effect is masked among those with severe pain because the pain-related sleep debt they acquire throughout the night then facilitates sleep onset the next day.